A large scale parallel fluid‐structure interaction computing platform for simulating structural responses to a detonation shock. (9th November 2021) - Zhang, Sen; Guo, Xiao‐Wei; Li, Chao; Liu, Yi; Fan, Sijiang; Zhao, Ran; Yang, Canqun
Abstract: Due to the intrinsic nature of multi‐physics, it is prohibitively complex to design and implement a simulation software platform for study of structural responses to a detonation shock. In this article, a partitioned fluid‐structure interaction computing platform is designed for parallel simulating structural responses to a detonation shock. The detonation and wave propagation are modeled in an open‐source multi‐component solver based on OpenFOAM and blastFoam, and the structural responses are simulated through the finite element library deal.II. To capture the interaction dynamics between the fluid and the structure, both solvers are adapted to preCICE. For improving the parallel performance of the computing platform, the inter‐solver data is exchanged by peer‐to‐peer communications and the intermediate server in conventional multi‐physics software is eliminated. Furthermore, the coupled solver with detonation support has been deployed on a computing cluster after considering the distributed data storage and load‐balancing between solvers. The 3D numerical result of structural responses to a detonation shock is presented and analyzed. On 256 processor cores, the speedup ratio of the simulations for a detonation shock reach 178.0 with 5.1 million of mesh cells and the parallel efficiency achieve 69.5%. The results demonstrate good potential of massively parallel simulations. Overall, a general‐purpose fluid‐structure interaction software platform with detonation support is proposed by integrating open source codes. And this work has important practical significance for engineering application in fields of construction blasting, mining, and so forth.